SPECIES DIVERSITY OF PUCCINIA PARASITIC ON PLANT FAMILY OF POACEAE IN NORTH-EASTERN OF UZBEKIST (British Journal of Global Ecology and Sustainable Development, 2023)
The article provides information about 15 species of the Puccini family distributed in 25 species of plants of the Poaceae family distributed in the North-Eastern region of Uzbekistan.